Pola Komunikasi Edukasi di Koperasi Unit Desa dan di Koperasi Pondok Pesantren - Wawan Lulus Setiawan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of this research is to describe the differences between the pattern of educational communication in the Village Unit Cooperatives (KUDs) and that in the Traditional Iskamic Boarding School Cooperatives (Kopontrens) in West Java Province, Indonesia. The research was carried out with qualitative approach on 12 KUDs and 12 Kopontrrens in West Java Province, Indonesia. The idea of research was based on the International and Indonesian Cooperative Principles which obliges the cooperatives to arrange cooperative education program for the cooperativeâ€™s members and based on the facts of cultural background differences between KUDs and Kopontrens. The result of the research indicated that educational communication in the Kopontrens is stronger than that in the KUDs because the process of educational communication process in the Kopontrens has become a standardized educational program, so that the elements of communication process consisting of â€œwho says what to whom in which channel, in what effect and environtmentâ€ has become a package of the educational communication curriculum in Kopontrens. This could explain why the membersâ€™ participation in the Kopontrens is better than that in the KUDs. This result of the study could give social and policy implication for developing method of members educatin in the KUDs in Indonesia.